Strategi Komunikasi Pemasaran Koran Samarinda Pos Di Tengah Pandemi Covid-19: Strategi Komunikasi Pemasaran Koran Samarinda Di Tengah Pandemi Covid-19 - Adi Busman Kadir (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2022)
This research is based on the influence of the Covid-19 pandemic which has a negative impact onvarious aspects of people's lives, one of which is the reduced income of mass media. Samarinda positself is a local newspaper in the city of Samarinda that carries criminal news. During the Covid-19pandemic, Samarinda Pos experienced a decrease in market percentage from before. In this case, ofcourse, Samarinda Pos requires a marketing communication strategy in order to survive in adifficult situation like this. So this study aims to find out the marketing communication strategy ofthe Samarinda Pos newspaper in the midst of the Covid-19 pandemic. This research is a qualitative descriptive research using observation, interview, and documentation data collection methods. Theuse of this type of research and data collection methods is so that researchers can describe and analyzethe strategies and impacts that exist in the Samarinda Pos newspaper. This research is also based onthe marketing mix theory (product, price, place, promotion) from Philip Kotler. Based on the resultsof the research and discussion, it can be seen that the marketing communication strategy carried outby Samarinda Pos during the Covid-19 pandemic on Samrinda Pos products is to create a digitalnewspaper / epaper that is accessed through the Samarinda website, as for the price of the newspaper,which is IDR 5,000 per copy with a total of 16 page and Samarinda Pos provide discounts to clientsaccording to the conditions of their respective companies, for the distribution of Samarinda Posnewspapers more at red-light intersections, the rest in government agencies, stalls, and so on, aswell as more passively spreading breaking news on social media Samarinda Pos, Then to carry outpromotions, Samarinda Pos held long-distance visits to clients and prospective clients by telephone.